Comparison of straight median sternotomy and interlocking sternotomy with respect to biomechanical stability - KÜÇÜKDURMAZ, FATİH; KÜÇÜKDURMAZ, FATİH; AĞIR, İSMAİL; BEZER, MURAT (My University, 2013)
AIM: To increase the stability of sternotomy and so decrease the complications because of instability.